Imaging behavior of facial deformities - Elizabeth Blanco Moredo; María Elena Gutiérrez Hernández; Carlos Valdés Collazo; Patricia Pérez Ramos; Lázaro Yunier Dunán Mesa (Medisur)
Background: For the surgical management of the patient with facial deformity, the use of the clinical and radiographic examination of each case is vital, since depending on the findings, a decision is made between the various therapeutic alternatives available in this field. Objective: to describe the imaging behavior of facial deformities in adult patients. Methods: a descriptive cross-sectional study was carried out in 46 patients older than 18 years old, with a diagnosis of facial deformity, who attended the Maxillofacial Surgery Service, Calixto García Hospital, from November 2017 to November 2019. The analyzed variables were: type of tissue, magnitude, and plane in which the alterations were evidenced. Fisher's exact test was used, with a confidence level of 95 %, to determine the analytical relationships between the variables; as well as Kendall's tau b and Spearman's Rho rates. Results: The 45.7 % of the deformities presented in both planes; 50 % of them with magnitudes between 11-30 mm; and in 41.3 % of the patients they affected the soft tissue. The correlations between the distribution of patients and the sets of variables plane/tissue type and plane/magnitude were weakly negative; while tissue type/magnitude presented a very significant moderate positive correlation, with significance values between 0.001 and 0.003. Conclusion: soft tissue deformities predominated, in both planes and with magnitudes between 11-30 mm. The imaging variables studied showed an interdependent behavior.